Gobierno, Justicia, Guerra y Hacienda: una nueva visión del “Indiferente General” del Archivo General de Indias - Moranchel Pocaterra, Mariana (Cuadernos de Historia del Derecho, 2007)
A new criteria to distribute by matters of government, justice, war and finances the documents that are contained into the subsection of “Indiferente General” that belongs to the Archivo General de Indias’ Government section. A new tool for the indianist researcher that allows him to save his time in the search of information.